The ability of elite table tennis players with intellectual disabilities to adapt their service/return - van Biesen, D.; Verellen, J.; Meyer, C.; Mactavish, J.; van de Vliet, P.; Vanlandewijck, Y. (Adapted Physical Activity Quarterly, 2010)
In this study the ability of elite table tennis players with intellectual disability (ID) to adapt their service/return to specific ball spin characteristics was investigated. This was done by examining the performance of 39 players with ID and a reference group of 8 players without ID on a standardized table tennis specific test battery. The battery included 16 sets of 15 identical serves that had to be returned to a fixed target, and two additional tests measuring reaction time and upper limb speed. A 2 × 4 ANOVA (with group and type of spin as independent variables) with repeated measurements (15 consecutive returns) supported the hypothesis that elite table tennis players with ID were significantly less proficient than their counterparts without ID, but both groups demonstrated a comparable progression in learning. Spearman correlation coefficients indicated a positive relationship between accuracy of return and upper limb speed (rho = 0.42: p < .05) and reaction time (rho = 0.41: p < .05), showing that these generic factors are useful in partially explaining skill variations in specific sports.